An investigation of the potential application of chitosan/aloe-based membranes for regenerative medicine - Silva, Simone Santos (2013)
A significant number of therapeutics derived from natural polymers and plants have been developed to replace or to be used in conjunction with existing dressing products. The use of the therapeutic properties of aloe vera could be very useful in the creation of active wound dressing materials. The present work was undertaken to examine issues concerning structural features, topography, enzymatic degradation behavior, antibacterial activity and cellular response of chitosan/aloe vera-based membranes. The chitosan/aloe vera-based membranes that were developed displayed satisfactory degradation, roughness, wettability and mechanical properties. A higher antibacterial potency was displayed by the blended membranes. Moreover, in vitro assays demonstrated that these blended membranes have good cell compatibility with primary human dermal fibroblasts. The chitosan/aloe vera-based membranes might be promising wound dressing materials.